Development of a Renewable Keratin-Based Adsorbent from Chicken Feather Waste for Cu(II), Zn(II), and Cd(II) Removal - Darjito; Ani Mulyasuryani; R. T. Tjahjanto; L.S.P. Sinambela; Yunir Ponco Prananto (The Journal of Pure and Applied Chemistry Research, 2026)
Development of keratin as an alternative of renewable adsorbent for metal ions is reported here. The keratin was isolated from sulfitolysis chicken feather waste using several concentrations of sodium sulfide. The isolated keratin was characterised by FTIR, SEM-EDX, and TGA. A batch-adsorption study of M(II) metal ions (M = Cd, Cu, Zn) in aqueous solutions was performed in various solution pH and contact time. Determination of the adsorption capacity of keratin toward each M(II) ions was performed at the optimum pH and contact time. This study reveals that the keratin was optimally obtained using sodium sulfide concentration of 2.0 M in a 49.89% yield. Batch-adsorption of M(II) ions (M = Cu, Zn, Cd) by the isolated keratin reaches optimum condition at pH 5 and contact time of 30 minutes for the Cu(II) and Cd(II) ions, and at pH 4 and contact time of 90 minutes for Zn(II) ion. Adsorption capacities of the synthesized keratin for Cu(II), Cd(II), and Zn(II) ions were (142.680 ± 2.307) mg/g, (151.318 ± 1.145) mg/g, and (156.803 ± 0.657) mg/g, respectively. Ongoing research on keratin functionalization is ongoing to enhance these adsorption capacities.